PERAN PSIKOLOGI DALAM PERKEMBANGAN KOGNITIF DAN LINGUISTIK PADA ANAK - Nurasia Natsir; Yuliyanah Sain; Aliah, Nuraziza (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
In human development, it is often characterized as a developmental milestone where new behaviors emerge and are increasingly complex as the stages of development appear in this modern era. Development does notoccur at a constant pace. A relatively fast growth (spurt) can be interspersed with slow growth (plateau).Some scholars use such uneven patterns of growth and change as evidence of qualitatively different periods of development. From the results of the study found 3 factors that have the potential to affect the development of each child's reasoning,namely; Hereditary factors (heredity), environmental factors, heredity and environmental factors that interact to form behavior. The characteristics inherited by each child have a sensitive period, namely when children are active and motivated learners and when children construct their knowledge based on experience. In implanting physical and cognitive devices there is thought and language becoming increasingly interdependent; As thought and language begin to fuse, children often talk to themselves which is known as self-talk. Self-talk has an important function in cognitive development: By talking to themselves, children learn to guide and direct their own behavior in the process of performing difficult tasks and performing complex maneuvers_just as adults guide them.